Konstruksi Berita Kasus Penembakan Enam Laskar FPI pada Tempo.co - Vicky Pratama Putra (PROPAGANDA, 2022)
The shooting incident that occurred between members of the Islamic Defenders Front (FPI) and the police caused the death of six members of the Soldiers, which became an interesting national issue to be reported on, because from the beginning of this case there were two versions released by both parties involved so that the media would construct their reality through what they see. The construction itself is part of the framing or media frame based on ideology, political views, and the vision and mission of the media itself and can be seen through the use of language as a highlight of meaning. This became the basis for a research entitled "Construction of News on the Shooting of the Six Laskar FPI on Media Tempo.co (Analysis of Framing Robert N. Entmann, period 7 December 2020 - 27 March 2021" with the formulation of the problem of how Tempo.co framed news of shooting cases six FPI troops on Tempo.co media. One research method that is able to support researchers in analyzing this case is a qualitative research method using the framing analysis method introduced by Robert N. Entman. Researchers want to see and understand how the construction of reality and other aspects built by the media to be conveyed to the public. The object of this research is the news of the shooting of six FPI soldiers published by the online media Tempo.co for the period 7 December 2020 - 27 March 2021.